The challenge of the sublime : From Burke's Philosophical Enquiry to British Romantic art - Pharabod-Ibata, Helene (Book collections on Project MUSE., 2018)
This interdisciplinary study looks at the influence of Edmund Burke's theories of the sublime on British Romantic art, arguing that it is far more significant than previously imagined.